Sistem Kendali Robot Pemadam Api Pintar menggunakan Metode Fuzzy Logic Tsukamoto - Agatha Deolika; Erik Setiawan (Journal of Information Technology, 2023)
The need for robots in the current era is very much needed because there are so many high-risk jobs. Fire extinguishing robots are one of them, very important because extinguishing fires is a risky job and requires precision. A fire extinguishing robot to find the location of the fire point must have efficient movement such as the speed at which the robot reaches the fire point. The robot's movement depends on its position on the arena or road, so that wasted movement often occurs which results in hitting walls or obstacles. In this research, the Tsukamoto method was applied to control robot speed based on sensors. After research and application of the Tsukamoto method, the robot can move efficiently with 90% accuracy.